The Dynamic Transcription Profiles of Proliferating Bovine Ovarian Granulosa When Exposed to Increased Levels of β-Hydroxybutyric Acid - Gong, Jianfei; Zhao, Shanjiang; Heng, Nuo; Wang, Yi; Hu, Zhihui; Wang, Huan; Zhu, Huabin (Frontiers in Veterinary Science, 2022)
Ketosis is common in high-yield dairy cows. It is a condition that is characterized by the accumulation of serum β-hydroxybutyric acid (BHBA). Both subclinical ketosis and clinical ketosis can compromise reproductive performance and cause long-lasting negative effects on reproductive efficiency by affecting the proliferation of follicular and granulosa cells. However, the regulatory mechanisms involved in the development of follicular cells and granulosa cells in cows experiencing subclinical ketosis and clinical ketosis remain largely unknown. To investigate the effect of ketosis-triggered increase in BHBA on bovine follicular granulosa cell development, we detected a significant reduction in the proliferation of granulosa cells (P < 0.05) in the BHBA-1.2 mM and BHBA-2.4 mM groups and a significant increase in the number of granulosa cells in the G1 phase of the cell cycle (P < 0.05). RNA-seq and trend analysis were used to identify differentially expressed genes by comparing three clusters: low-does response to 1.2 mM BHBA, high-does response to 2.4 mM BHBA, and the consistent trend response to increasing BHBA. GO and KEGG enrichment analysis were performed separately for each cluster. Analysis showed that two novel down-regulated genes (G0S2 and S100A6), which are associated with cell proliferation and cycle progression, were enriched in the low-does response to 1.2 mM BHBA. Another differentially expressed gene (PARP), which plays a role in the apoptotic pathway, was enriched in the high-does response to 2.4 mM BHBA. We also found that CYP27B1 and CYP17A1, which are associated with Ca2+ homeostasis and estrogen synthesis, were enriched in the consistent trend response. In conclusion, we describe the dynamic transcription profiles of granulosa cells under different levels of β-hydroxybutyric stress and report key regulators that may underlie the detrimental effects on the development of follicles and granulosa cells, thus representing potential therapeutic targets to improve fertility in dairy cows with subclinical ketosis or clinical ketosis.